مراكز انتاج الفخار في شبه الجزيرة العربية: دراسة في أحد مصادر تاريخ العرب قبل الإسلام (Journal of Academic Research, 2024)
The importance of archaeological sources, especially pottery finds, is due to them being the tangible material expression of human life, and they relate to all aspects of life and its fields. Their archaeological remains, which were found in various sites in the Arabian Peninsula, helped write the history of the Arabs before Islam. Many cultural centers spread in the east of the Arabian Peninsula, producing different types and types of pottery, the most important of which is the Umm al-Nar site, whose industry spread in various regions of the Arabian Gulf, as well as the Ubaid civilization, which is attributed to the Tell al-Ubaid site in southern Iraq. Ubaid pottery is considered One of the oldest types of pottery found in sites on the western Gulf coast. Also, the location of Barbar is in the far northwest of Bahrain Island, and its red pottery is considered one of the most important elements of the Dilmun civilization, which flourished at the end of the third millennium and the beginning of the second millennium BC. It is one of the most important centers of pottery production in the north of the Arabian Peninsula. Nabataean pottery spread in various regions of the eastern Arabian Gulf and in the eastern parts of the Arabian Peninsula, which indicates the existence of trade relations between the Nabataean Kingdom and those parts of the Arabian Peninsula. As for the pottery of southern Arabia, it was known as the cultural centers of The village of Al-Faw is considered one of the most important centers of pottery production in the central Arabian Peninsula. The pottery finds that were found in Al-Faw showed the extent of its richness and cultural development, and confirmed the existence of aspects of factors of influence and influence with the cultural centers neighboring it.